2019
DOI: 10.1039/c9cc07405h
|View full text |Cite
|
Sign up to set email alerts
|

Chemo-enzymatic three-step conversion of glucose to kojic acid

Abstract: A method for producing kojic acid from glucose via glucosone using a chemo-enzymatic three-step approach was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…26,27 The crude D-glucosone, obtained from MetGen Oy, was only subjected to ltration through a 0.45 micron lter in order to remove enzyme particles aer the enzymatic process where D-glucose is oxidized to D-glucosone. 6 A portion of the crude D-glucosone was then further puried by column chromatography to obtain the puried D-glucosone used in the hydrogenation test reactions. The catalysts screened in the batch reactor were Ru/C, Ru/Al 2 O 3 , Ru on nitrogen doped carbon nanotubes (NCNT), Cu/SiO 2 , and RANEY® nickel.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…26,27 The crude D-glucosone, obtained from MetGen Oy, was only subjected to ltration through a 0.45 micron lter in order to remove enzyme particles aer the enzymatic process where D-glucose is oxidized to D-glucosone. 6 A portion of the crude D-glucosone was then further puried by column chromatography to obtain the puried D-glucosone used in the hydrogenation test reactions. The catalysts screened in the batch reactor were Ru/C, Ru/Al 2 O 3 , Ru on nitrogen doped carbon nanotubes (NCNT), Cu/SiO 2 , and RANEY® nickel.…”
Section: Resultsmentioning
confidence: 99%
“…The smaller pores are blocked entirely due to fouling, increasing the apparent average pore size measured by nitrogen physisorption. Previously, it has been shown that D-glucosone has a tendency to oligomerize or polymerize at temperatures above 50 C. 6 The difference in mass balance closures probably results from the formation of polymers, which are deposited on the walls and adsorbed on the catalyst due to low solubility in water, resulting in fouling.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations